Computed tomography angiography of the coronary arteries: major findings in the clinical routine of a general hospital - Souto,Rafael Mansur (2021)
Abstract Almost two decades ago, it became possible to use coronary computed tomography for the noninvasive assessment of the coronary arteries. That is an extremely accurate method for detecting or excluding coronary artery disease, even the subclinical forms. This pictorial essay aims to show the main imaging findings in 47 coronary computed tomography scans acquired at a general hospital between January 2014 and June 2018. The most common findings were atheromatous plaques (in 87%) and stents (in 34%). There were also incidental findings, not directly related to coronary artery disease, such as pulmonary nodules and aortic stenosis.